2022
DOI: 10.3390/foods11152222
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Implementing the MySusCof App—A Mobile App to Support Food Waste Reduction

Abstract: Consumers are responsible for almost 50 percent of food waste. Consumer-focused interventions are crucial to achieve many Sustainable Development Goals (SDGs), especially SDG 12.3. There are many factors that cause food waste, and these can be prevented by changing the consumption behavior of adults. Mobile apps are seen as promising tools to change consumer behavior for ensuring more sustainable food consumption. This study describes the development process and examines the perceived quality of MySusCof, an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Haas et al. (2022) develop a new FWMA called MySusCof offering food management information and tips to reduce food waste.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haas et al. (2022) develop a new FWMA called MySusCof offering food management information and tips to reduce food waste.…”
Section: Resultsmentioning
confidence: 99%
“…Practical testing showed that the process of food waste collection was simpler with the help of the mobile application and the gamified design incentivized people in the community to learn and adapt a proper way to dispose of food waste; this helped the government with food waste compliance monitoring. Haas et al (2022) develop a new FWMA called MySusCof offering food management information and tips to reduce food waste. Users gain credits by completing food purchasing and food management tasks.…”
Section: Mobile Applicationsmentioning
confidence: 99%
“…It is not about partial strategies but about launching collective projects that are both multi-and interdisciplinary. Although there is an app (MySusCof) [59] focused on educating people about the sustainability potential of food waste, there is currently no app that enables simultaneous education on sustainability (highlighting the importance of utilizing food waste), nutrition (promoting healthy eating), and culinary skills (facilitating the creation of recipes with the foods available to consumers, automatically). The use of food waste for charity canteens from Valencia with Foodration4all [60] is proposed, where the charity uses a blockchain application to purchase cards to obtain food/reduce food waste [70].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the results were focused on sustainability, corresponding to the initial "S" in the acronym MagNuS project. This project has identified four steps that could be taken to achieve the sustainability goal set out in the technical guide about sustainability in the Valencia Conference Center, as follows: (i) that the catering company uses of the Too Good To Go app to help reduce food waste and CO 2 emissions and to allow the general public to access quality products at an affordable price [58], (ii) the Center could raise awareness among its events' attendees with a mobile app called MySusCof, thus applying sustainability education to reduce the food waste of consumers [59], (iii) the leftover food could be used in charity canteens in Valencia by Foodration4all [60], and (iv) the Center could create compost from the food waste [61] and use it in the gardens on-site.…”
Section: Assessment Of Nutritional Content and Sustainabilitymentioning
confidence: 99%
“…Five of them, i.e., FoodKeeper [20], CozZo [21], Fridge Pal [22], No Waste [23], and StillTasty [24], were still available online in 2022, while others, i.e., Pantry [19] and Green Egg [25], are no longer available or maintained. It is worth mentioning that several apps are documented in the scientific literature as prototypes (e.g., EatChaFood [26], Pantry [19], MySus-Cof [27]), but nevertheless address many theoretical and practical aspects of the application design process. The five tools still available address food inventory management through one or more functionalities: (a) organising purchased products based on expiration date, (b) organising household food needs in shopping lists, and (c) suggestions for using up leftovers and products about to expire (Table 1).…”
Section: Introductionmentioning
confidence: 99%